Whole blood stabilization for the microfluidic isolation and molecular characterization of circulating tumor cells. Issue 1 (December 2017) - Wong, Keith; Tessier, Shannon; Miyamoto, David; Miller, Kathleen; Bookstaver, Lauren; Carey, Thomas; Stannard, Cleo; Thapar, Vishal; Tai, Eric; Vo, Kevin; Emmons, Erin; Pleskow, Haley; et al.
Abstract Precise rare-cell technologies require the blood to be processed immediately or be stabilized with fixatives. Such restrictions limit the translation of circulating tumor cell (CTC)-based liquid biopsy assays that provide accurate molecular data in guiding clinical decisions. Here we describe a method to preserve whole blood in its minimally altered state by combining hypothermic preservation with targeted strategies that counter cooling-induced platelet activation. Using this method, whole blood preserved for up to 72 h can be readily processed for microfluidic sorting without compromising CTC yield and viability. The tumor cells retain high-quality intact RNA suitable for single-cell RT-qPCR as well as RNA-Seq, enabling the reliable detection of cancer-specific transcripts including the androgen-receptor splice variant 7 in a cohort of prostate cancer patients with an overall concordance of 92% between fresh and preserved blood. This work will serve as a springboard for the dissemination of diverse blood-based diagnostics. The current FDA-approved whole blood stabilization method for circulating tumor cell (CTC) isolation suffers from RNA degradation. Here the authors combine hypothermic preservation and antiplatelet strategies to stabilize whole blood up to 72 h without compromising CTC yield and RNA integrity.